Engineering of Pentose Transport in Saccharomyces cerevisiae for Biotechnological Applications - Nijland, Jeroen G.; Driessen, Arnold J. M. (Frontiers in Bioengineering and Biotechnology, 2020)
Lignocellulosic biomass yields after hydrolysis, besides the hexose D-glucose, D-xylose and L-arabinose as main pentose sugars. In second generation bioethanol production utilizing the yeast Saccharomyces cerevisiae, it is critical that all three sugars are co-consumed to obtain an economically feasible and robust process. Since S. cerevisiae is unable to metabolize pentose sugars, metabolic pathway engineering has been employed to introduce the respective pathways for D-xylose and L-arabinose metabolism. However, S. cerevisiae lacks specific pentose transporters, and these sugars enter the cell with low affinity via glucose transporters of the Hxt family. Therefore, in the presence of D-glucose, utilization of D-xylose and L-arabinose is poor as the Hxt transporters prefer D-glucose. To solve this problem, heterologous expression of pentose transporters has been attempted but often with limited success due to poor expression and stability, and/or low turnover. A more successful approach is the engineering of the endogenous Hxt transporter family and evolutionary selection for D-glucose insensitive growth on pentose sugars. This has led to the identification of a critical and conserved asparagine residue in Hxt transporters that, when mutated, reduces the D-glucose affinity while leaving the D-xylose affinity mostly unaltered. Likewise, mutant Gal2 transporter have been selected supporting specific uptake of L-arabinose. In fermentation experiments, the transporter mutants support efficient uptake and consumption of pentose sugars, and even co-consumption of D-xylose and D-glucose when used at industrial concentrations. Further improvements are obtained by interfering with the post-translational inactivation of Hxt transporters at high or low D-glucose concentrations. Transporter engineering solved major limitations in pentose transport in yeast, now allowing for co-consumption of sugars that is limited only by the rates of primary metabolism. This paves the way for a more economical second-generation biofuels production process.